2017
DOI: 10.1111/gtc.12504
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive yet nonuniform contributions of Dcp2 and Cnot7 to maternal mRNA clearance in zebrafish

Abstract: mRNA degradation is a fundamental biological process that erases transcribed genetic information from cells. During maternal-to-zygotic transition of animal development, thousands of maternal mRNAs are degraded by multiple mechanisms including microRNAs and codonmediated decay. Enzymatic requirements for maternal mRNA clearance, however, are not fully understood. Here, we analyzed a contribution of the decapping enzyme Dcp2 to maternal mRNA clearance in zebrafish by over-expressing catalytically inactive Dcp2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
(77 reference statements)
1
9
0
Order By: Relevance
“…Although the degradation of mRNA generally proceeds from both 5 0 and 3 0 ends, our study demonstrates that the shortening of poly(A) tails by the CCR4-NOT deadenylase complex contributes substantially to the post-transcriptional regulation of hairy-related mRNAs compared with the decapping by Dcp2 in zebrafish segmentation clock. This observation is consistent with the differential contributions of the two decay machineries to maternal mRNA decay [23]. By using transgenic embryos, mRNAs derived from reporter genes fused to the 3 0 UTRs of her1, her7, and hes6 essentially recapitulated the turnover of endogenous transcripts predicted by the PAT assay (Fig.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Although the degradation of mRNA generally proceeds from both 5 0 and 3 0 ends, our study demonstrates that the shortening of poly(A) tails by the CCR4-NOT deadenylase complex contributes substantially to the post-transcriptional regulation of hairy-related mRNAs compared with the decapping by Dcp2 in zebrafish segmentation clock. This observation is consistent with the differential contributions of the two decay machineries to maternal mRNA decay [23]. By using transgenic embryos, mRNAs derived from reporter genes fused to the 3 0 UTRs of her1, her7, and hes6 essentially recapitulated the turnover of endogenous transcripts predicted by the PAT assay (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…The removal of 5 0 cap structure of mRNA also plays a critical role in the degradation of eukaryotic mRNA from 5 0 end. To examine whether the functional interferences of decapping may affect the somite segmentation as was observed in cnot7-DN mRNAinjected embryos, we overexpressed mRNA encoding a dominant negative form of the decapping enzyme, Dcp2 (Dcp2-DN), which has been shown to increase the stability of maternal RNAs in zebrafish [23]. Although the injection of dcp2-DN mRNA perturbed the embryogenesis at 24 hpf as described previously [23], we did not observe any defective segmentation of the somites in dcp2-DN mRNA-injected embryos ( Fig.…”
Section: Defective Somite Segmentation By the Inhibition Of The Ccr4-mentioning
confidence: 99%
See 1 more Smart Citation
“…CNOT7 mRNA is a maternal RNA which translates to a key component of deadenylation machinery involved in maternal mRNA clearance (Ma et al . 2015; Mishima and Tomari 2017). Ortholog of FGF20 in Nile tilapia specifically expresses in female gonads and its mRNA accumulates in the cytoplasm of growing oocytes (Sun et al .…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown that inherent RNA properties, such as transcript and polyA-tail length, codon usage and RNA structure influence RNA stability (Mishima & Tomari, 2016;Bazzini et al, 2016;Subtelny et al, 2014;Mishima & Tomari, 2017). To investigate whether Ski7 targets share specific transcript features that make them prone for Ski7-dependent regulation, we assessed whether shared period DEGs differ in their intrinsic RNA properties compared to unchanged genes.…”
Section: Ski7 Targets Transcripts With Diverse Featuresmentioning
confidence: 99%